Real-world treatment patterns and survival outcomes in patients with locally advanced squamous cell carcinoma of the head and neck in Germany using claims data - Hering, Kathrin; Kuhnt, Thomas; Kossack, Nils; Richter, Lena M.; Schultze, Michael; Osowski, Ulrike; Henkel, Luisa; Gaupel, Ann-Christin; Solbes, Marie-Noelle; Zolyniak, Bernard; Schoenherr, Nancy (Frontiers in Oncology, 2025)
IntroductionStandard-of-care treatment for locally advanced squamous cell carcinoma of the head and neck (LA SCCHN) is surgery with consolidation chemoradiotherapy (CRT) or definitive CRT. There is a paucity of real-world evidence regarding current treatment patterns and downstream outcomes for LA SCCHN in German clinical practice.MethodsThis study was a non-interventional, observational, retrospective cohort study of newly diagnosed patients with LA SCCHN using routinely collected claims data from a health insurance claims database in Germany (2016–2021). Claim records were used to describe the cohort, including incidence, characteristics, treatment patterns, and survival. As permitted by the data, descriptive analyses were stratified by index treatment (surgical resection or definitive non-surgical treatment), tumor site (oral cavity, oropharynx, hypopharynx, or larynx), and sex. The study was descriptive in nature; as such, no statistical comparisons were made.ResultsThe LA SCCHN cohort comprised 1,010 patients (827 male and 183 female patients), of whom 39.8% (402/1,010) received surgical resection and 60.2% (608/1,010) received definitive non-surgical treatment as part of index treatment. Patients with surgical resection as part of index treatment were characterized by a younger mean age and lower comorbidity indices. After index treatment, three-quarters (74.8%) of the study population received no subsequent SCCHN treatment. Index treatment was similar for male and female patients. The rate of surgical resection and definitive non-surgical treatment was similar in patients with oral cavity cancer [50.6% (128/253) and 49.4% (125/253), respectively]; all other tumor sites were treated more frequently (>60%) with definitive non-surgical treatment. The 5-year probability of survival for the overall population was 48.5% (95% CI: 44.4%–53.1%). Survival probabilities varied across tumor sites and by index treatment.ConclusionDespite index treatment being broadly aligned to guideline recommendations, most patients did not receive a subsequent line of treatment and almost half of patients had died within 5 years. This highlights the urgent unmet need for improved treatment options for LA SCCHN.